Clinical and Radiographic Evaluation of Success Rate with MTA Plug in Open Apices - Ghaziani, Pari; Fallah Rastegar, Akbar; Bidar, Maryam; Sadeghi, Ghazal; Chegin, Parviz (Iranian Endodontic Journal, 2010)
INTRODUCTION: The ideal endodontic treatment for the teeth with in complete root-ends and necrotic pulps may involve the use of material which forms an immediate apical barrier instead of long term calcium hydroxide therapy. Such procedure may lead us to a single appointment endodontic treatment. The purpose of the present study was to evaluate clinical and radiographic success rate in necrotic teeth with open apices treated with MTA as an apical plug. MATERIALS AND METHODS: Thirty five patients between the ages of 8-16 with total number of 41 necrotic anterior teeth containing open apices were selected. In the first visit, root canals were debrided and filled with calcium hydroxide. After one week, calcium hydroxide was removed and MTA with the thickness of 3 to 4 mm was put in the apical region of the canals. After 24 hours, the remaining part of the canals was filled with guttapercha and sealer and the teeth were restored with composite. All the cases were evaluated clinically and radiographically after 3 and 6 months and data were analyzed by McNemar test. RESULTS: No clinical symptoms were observed in 97.6% of the teeth after 3 months and in none after 6 months. The study showed a significant difference from pretreatment status. After 3 months radiographic evaluation showed that in 17 cases (41.5%), lesions were reduced and in 14 cases (34.1 %), lesions remained the same, and in 10 cases (24.4%) lesions disappeared. After 6 months in 21 cases (51.2%), lesions were reduced, in 3 cases (7.3%) lesions remained the same and in 17 cases (41.5%) lesions disappeared. These finding were statistically different from pretreatment data. CONCLUSION: The results indicate that MTA can be used as an apical plug in the teeth with open apices following root canal debridement and disinfection with calcium hydroxide. Further investigations with longer follow-ups are recommended in order to evaluate the effect of this material.